The Theme of Love in Kaygusuz Abdâl’s Dîvân - Kurtoğlu, Fadime; Söylemez, İsmail (Journal of Alevism-Bektashism Studies, 2025)
This article examines the representations, symbolic dimensions, and mystical layers of meaning of the concept of love (ʿishq) in the Dīvān of Kaygusuz Abdâl, one of the prominent Sufi poets who lived in the late fourteenth and early fifteenth centuries. Kaygusuz Abdâl interprets love as a fundamental principle guiding humanity toward divine truth and as a transformative force in the process of returning to the essence of being. He conceives love as both the source and the manifestation of the eternal bond between human beings and God. In his poetry, love functions as the primary means through which existence returns to its origin, the self is annihilated, and the knowledge of truth is attained. Moreover, the heart (gönül), which emerges prominently in the poems as the locus of divine manifestation, is positioned as the sole dwelling place of love.The poet’s use of vernacular language, didactic tone, direct address, and allegorical narration brings the abstract concept of love into the realm of concrete experience. In this respect, Kaygusuz Abdâl approaches mystical love not merely as a metaphysical notion but also as an inner process of human transformation. In the poems of the Dīvān, love is treated on both “metaphorical” (mecazi) and “true” (hakiki) levels, skillfully weaving transitions between worldly affection and divine love. The language employed by the poet combines the aesthetic structure of classical poetry with elements of folk expression, thereby creating an original mystical style. Within this linguistic framework, love becomes a symbol of seeking, burning, and purification.In the Dīvān of Kaygusuz Abdâl, love is not only a thematic element but also the central component of the transformative process through which the human being is purified of the self and attains absolute being in accordance with the doctrine of waḥdat al-wujūd (the unity of existence). Through selected couplets from the Dīvān, this study analyzes the relationship of love with the concepts of its “nature,” “outcome,” “poetic aesthetics,” “its locus of manifestation in the human being,” and its “path.” In this context, the article aims to render visible the multilayered structure of love by employing text-centered analysis alongside Sufi interpretative methods. The findings highlight Kaygusuz Abdâl’s distinctive position within the tradition of Sufi poetry and reveal the depth of his conception of love.
Keywords: Kaygusuz Abdâl Divanı; Sufism; Love; Divine Love; Metaphorical Love